Synthesis of 3-halogenated 2, 3′-biindoles by a copper-mediated 2, 3-difunctionalization of indoles. Issue 47 (29th November 2021) - Zhang, Xiaoxiang; Zhang, Yingying; Gu, Xiaoting; Zhang, Zhuan; Wei, Wanxing; Liang, Taoyuan
Abstract : A copper-mediated 2, 3-difunctionalization of indoles to afford 3-halogenated 2, 3′-biindoles was developed, which established a good foundation for further chemical transformation. Abstract : A copper-mediated 2, 3-difunctionalization of indoles to afford 3-halogenated 2, 3′-biindoles is described herein. The protocol uses readily available feedstocks and a naturally abundant copper catalyst system, which allows the regioselective formation of C–C and C–X (X = Cl & Br) bonds in one single operation. Here the copper metal salt serves not only as a catalyst but also as a reactant to provide the source of halogen. This operationally simple procedure avoids the utilization of environmentally unfriendly reagents and displays good functional group compatibility. Noteworthily, the introduction of halogen into molecules would offer great potential for further chemical transformations.